A General Look At The Environment And Environmental Problems In Tourism - Yazıcı, Hacer Neyir (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2011)
In literature, environment is mentioned as "the whole nature and examples of human-made structures in the nature together with human beings and all other living beings". Environment is the atmosphere or conditions in which an organism exists and it is an atmosphere that existed with the first living being on earth. Environment is the physical, biological, social, economic and cultural atmosphere where people and other living beings lead their lives and interact with one another. Human life is built on various balances. Breaks that occur in the links that form the natural balance which people establish with their nature affect the whole chain, lead to defects in this balance and cause environmental problems. Basic environmental problems that people face can be summarized as follows: Increasing pollution of the air, water and earth and an important part of them becoming unusable, big cities' and industrial areas' becoming impossible places to live in due to environmental pollution, ozone layer depletion, increasing global warming, increase in cancer and similar diseases, fast consumption of natural resources, etc. Although. the developing industrial sector is shown as the primary perpetrator of environmental problems, tourism, which is referred to as the industry without a chimney, also affects the environment negatively. Tourism, which is closely related to the environment in terms of its sustainability, generally seeks after short term benefits during the marketing of resources and it can harm these resources - which are its raw material. Tourism, which is the user, not the protector, of tourism in its development process, caused concerns about the environment since it helps economic development in developing and underdeveloped countries including Turkey. In this study, environment and environmental problems arising out of tourism will be touched upon, the problems caused on tourism by environmental problems will also be analyzed and the tourism dimension of environment and its problems will be reflected in the study with an extensive literature study.
Keywords: tourism; environment; tourism and environment; turizm; çevre; turizm ve çevre